Existence of Solution for a Coupled System of Fractional Integro-Differential Equations on an Unbounded Domain (Analysis in Theory and Applications, 2013)
We present the existence of solution for a coupled system of fractional integro-differential equations. The differential operator is taken in the Caputo fractional sense. We combine the diagonalization method with Arzela-Ascoli theorem to show a fixed point theorem of Schauder.
Keywords: Fractional derivative (integral); coupled system; Volterra integral equation; diagonalization method.